Pemahaman Mekanisme dan Penerapan Pembukaan Rekening Efek Kepada Siwa dan Guru SMK Panca Dharma, Kota Balikpapan - Dessy Handa Sari; Endang Sri Apriani; Nurul Musfirah Khairiyah; Kety Lulu Agustin; Ida Suriana (Journal of Applied Community Engagement, 2023)
Securities companies, also called stock companies, are the most important chain in the capital market industry. Its existence is needed by two other market players, namely institutions (both government and private) that wish to raise funds and parties who have funds, both creditors and debtors. Unfortunately, literacy about stock investment is still low, especially in the younger generation, specifically in vocational schools in Balikpapan. For that reason, the Non-Productive Community Empowerment Program (PPM-NP) was held to empower target audiences to have knowledge about the importance of using free time in positive activities that can increase knowledge and skills. The target audience for this activity is Panca Dharma students in Balikpapan. This activity is collaborative with Mirae Balikpapan securities companies. This dedication method is carried out by providing training materials in lectures about the importance of introducing securities accounts on the stock exchange and the practice of opening securities accounts by several teachers and students of Panca Dharma Vocational School, which amounts to forty people who collaborate with Mirae Securities companies. The end result of this community dedication program is additional literacy and related education for teachers at the Panca Dharma Balikpapan Vocational School and the opening of securities accounts by five teachers and 18 students.